The introduction of a new curriculum in Western Switzerland public scholls and its implication on the practices of teacher educators - Melfi, Giuseppe; Giglio, Marcelo (My University, 2014)
We studied the implications of the introduction of a new curriculum in Western Switzerland public schools in 2011. We analyze the degree of difficulty of teacher trainers with the main propositions of the Plan d’Etude Romand (PER) that is at present the new curriculum in French speaking part of Switzerland (West). We compare the degree of difficulties of teacher trainers, measured by means of a Likert scale, for a series of components, requirements and aspects of the PER. Furthermore, we consider three groups of teacher trainers, depending on their main function as professionals of education, and we found the degrees of difficulties depend on the characteristics and the profile of trainers.
, EAPRIL 2012 Conference (European Association for Practitioner Research on Improving Learning), Nicosia